Milk Ship Returns: 101 Young Midshipmen End Mercy Cruise to France, Intaly and Greece - Foisie, Jack (San Francisco Chronicle)
California's "milk ship," the Golden Bear, came home to San Francisco yesterday, ending her four month's goodwill trip to Europe.